Community Medicine and Family Health Department, Maharajgunj Campus, Institute of Medicine , Tribhuwan University - Sapkota, VP; Gurung, CK (Journal of Nepal Health Research Council, 2010)
Background: Malnutrition is a major underlying cause of the child morbidity and mortality in Nepal. In the past ten years there hasn’t been any significant progress in the nutritional status of the under-fives in Nepal. In such situation this study determines the prevalence of undernutrition and the factors associated with it which helps district health managers monitor undernutrition and identify different associated factors essential in order to better design and implement the nutritional interventions. Methods: A cross-sectional comparative study was conducted in Belahara VDC among 150 underfive children in 2008. Primary caretakers were interviewed for different socio-demographic and maternal & child health related factors. Through anthropometry, prevalence of underweight, stunting and wasting was determined. Logistic regression statistical tool was used to analyze the influence of different predictors. Results: Prevalence of underweight, stunting and wasting was 27%, 37% and 11% respectively. In the final model of logistic regression statistical tool, male sex was found protective for stunting. Comparatively, the risk of being underweight in the children from the poor socioeconomic status is almost four times as much as in the children from the rich socioeconomic status [OR= 4.336 (1.719 <OR<10.936)]. Children from joint family were found protective against stunting than children in the nuclear family. Other covariates such as age at pregnancy and ethnicity of the child were found to be significantly associated only at 10% level of significance. Conclusion: Acute undernutrition was found more in the VDC as of national figure. Emphasis should be placed on the girl children and the disadvantaged ethnic groups for nutritional interventions. These interventions should be coordinated with income generation and food production activities for sustainability of nutritional interventions. Maternal age at pregnancy, as found determining the nutritional status of children, should be included as a part of nutrition counseling during ANC visits. Key words: Underweight; stunting; wasting; predictors; nutritional intervention DOI: 10.3126/jnhrc.v7i2.3020 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 120-126